Prevalence of Tobacco and associated risk factors among university law students in Indore City - Sonali Gupta; Prashant Mishra; Sandesh Nagarajappa; Sandeep Kumar; Afsheen Lalani (Wolters Kluwer Medknow Publications, 2019)
Introduction: Tobacco use is one of the major preventable causes of death and disability worldwide. The practice of law can be demanding and exceedingly stressful. Trends in tobacco use among young people are important to document because these findings will help inform the development of appropriate preventive intervention programs for youth. Aim: To assess prevalence of tobacco and associated risk factors among university law students in Indore city. Objective: To identify the strength of association related to tobacco consumption. Materials and Methods: A descriptive cross-sectional study was conducted among 278 law students in Indore city using convenient sampling technique. The data was collected using pre-tested close ended self-administered questionnaire. Frequency distribution analysis was performed. Bivariate analysis was done followed by logistic regression analysis. The level of significance for all the tests was set at P < 0.05. Results: The present study revealed that 32% of the study subjects consumed smoking tobacco as compared to 2.5% of smokeless tobacco. Nearly two-third of the law students consumed tobacco at public places 185 (66.5%) under the influence of friends. Only 18 (6.5%) study subjects tried to quit tobacco in the last 12 months whereas 65 (23.4%) of them never wanted to quit the habit of tobacco consumption. A bivariate analysis was performed to identify the risk factors related to tobacco consumption. It was found that male individuals (OR=2.04, P =0.004*) whose family members had the habit of tobacco consumption (OR=2.9, P =0.002*) were at a higher risk for consuming tobacco. The factors that became significant in bivariate analysis were then entered in logistic regression analysis [Enter method] to identify the strength of association. The individuals who had the habit of tobacco consumption among family members emerged as the strongest risk predictor leading to tobacco consumption amongst the students. Conclusion: The present study revealed that smoking form of tobacco consumption (cigarette- 32%) was more prevalent among the male study subjects under the influence of friends and with family members who had the habit of consuming tobacco at their place of residence.